Characterization of Cottage Textile Dyeing Effluent of Sirajganj District in Bangladesh - Islam, Md Zohurul; Hasan, Md Rashidul; Mostafa, Md Golam (Al-Nahrain Journal of Science, 2024)
The textile dying industry is one of the most important industrial sectors in Bangladesh. The discharged untreated effluent from different industries adds to the environment a wide variety of harmful chemicals, which cause severe damage to the water. The present study aimed to characterize the discharged effluent surrounding the areas of cottage textile dyeing industries. The effluent samples were collected from different locations of the four upazilas (administrative regions) in Sirajganj district in three seasons, namely the pre-monsoon, monsoon, and post-monsoon, covering two years. The study considered the major physicochemical and chemical parameters, including biological oxygen demand (BOD), chemical oxygen demand (COD), heavy metals, and anions. The analysis results showed that most of the physicochemical parameters, including EC, pH, TDS, TSS, turbidity, BOD, COD, organic matter (OM), total hardness (TH), the cationic and anionic parameters, and trace metals, including Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Cd, and Pb, in effluent samples exceeded the Department of Environment, Bangladesh (DoE-BD) standard, 2008. The most toxic heavy metals, such as Cr, Mn, Cd, and Pb, were found to be higher than the standard permissible limit in all of the collected samples, indicating heavy metal pollution in the area. The analysis results of the Fourier-transform infrared spectroscopy (FTIR) showed that the effluent samples contained toxic functional groups, like azo, cyano, etc., indicating higher levels of pollution due to the discharge of untreated textile dyeing effluent.